2005
DOI: 10.1038/sj.ejcn.1602159
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of folic acid from fortified pasteurised and UHT-treated milk in humans

Abstract: Objective: The aim of this study was to investigate whether milk fortified with folic acid enhances the folate status of humans and whether the presence of folate-binding proteins (FBP) in pasteurised milk affects the bioavailability of folic acid from fortified milk. In untreated and pasteurised milk, folate occurs bound to FBP, while FBP is (partly) denatured in ultra-high-temperature (UHT)-treated milk. The effect of FBP on folate bioavailability is still unclear. Design, subjects and setting: Healthy, free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 45 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…For instance, in different studies of healthy populations using the same follow-up interval (de Jong et al [ 75 ] and Schorah et al [ 76 ]), the population with the lower baseline folate concentration (8.6 vs. 19.7 nmol/L) demonstrated the greater increase (64% vs. 47%). Analysing data from 13 studies, Wald et al found a greater proportional increase in serum folate for those with lower baseline concentrations [ 87 ].…”
Section: Response To Supplementation and Fortificationmentioning
confidence: 99%
“…For instance, in different studies of healthy populations using the same follow-up interval (de Jong et al [ 75 ] and Schorah et al [ 76 ]), the population with the lower baseline folate concentration (8.6 vs. 19.7 nmol/L) demonstrated the greater increase (64% vs. 47%). Analysing data from 13 studies, Wald et al found a greater proportional increase in serum folate for those with lower baseline concentrations [ 87 ].…”
Section: Response To Supplementation and Fortificationmentioning
confidence: 99%
“…The numerous approaches, having specifi c advantages and limitations, can provide information on folate bioavailability to different extents (Table 2.2 ). In food -related research, it is diffi cult to carry out double -blind randomized controlled intervention trials [58] . It is important to control compliance, choice of the intervention period (preferably three or more months, especially when slowresponding erythrocyte folate concentrations are used for status assessment), and choice of suitable endpoint/status parameters when designing an intervention study.…”
Section: Models/methods To Determine Folate Bioavailabilitymentioning
confidence: 99%
“…It is important to control compliance, choice of the intervention period (preferably three or more months, especially when slowresponding erythrocyte folate concentrations are used for status assessment), and choice of suitable endpoint/status parameters when designing an intervention study. High bioavailabilities of endogenous folates from vegetables and fruits [59,60] , rye cereal products and orange juice [61] , folic acid -fortifi ed milk [58,62] , and folic acid -fortifi ed breakfast rolls [63] have been reported using different intervention models. Also, the effects of dietary polyglutamyl folates [64] and different folate supplements [65] on folate status have been studied.…”
Section: Models/methods To Determine Folate Bioavailabilitymentioning
confidence: 99%
“…It was suggested from animal experiments that the addition of FBP-rich foods to folate-rich foods could enhance the bioavailability of folates, but the outcome of such a combination would depend on interactions with other components of the diet [44]. Although milk is a suitable matrix for folic acid fortification to enhance folate status, no significant effect of endogenous FBP was found on the bioavailability of folic acid from milk [45].…”
Section: Folate: An Important Vitaminmentioning
confidence: 98%